Efeito da temperatura de encharque no recozimento contínuo e da deformação na laminação de encruamento sobre as propriedades mecânicas de um aço microligado laminado a frio - Rogerio Carlos Oliveira Fernandes (2007)
The obtainment of adequate mechanical properties in high strength steels depends as much on the chemical compositions as on the process variables. In the specific case of HSLA (high strength low alloy) steels, the importance of the process variables is even more significant, because of the several strengthening mechanisms involved (solid solution, precipitation, grain refinement and dislocation density). This study investigates the influence of soaking temperature in the continuous annealing process and elongation in the skin pass mill (SPM) on the mechanical properties of a HSLA steel, microalloyed with niobium, of the class of 340 MPa minimum yield stress. Three different thermal cycles and five levels of elongation at SPM were evaluated. The results indicate that the mechanical properties of this steel are significantly affected as much by the soaking conditions as by the SPM elongation, mainly the yield stress and the total elongation